234k views
4 votes
Let f(x) = 12x5 − 36x4 − 6x3 and g(x) = 6x2. Find f of x over g of x.

2x2 + 6x + 1
2x2 − 6x − 1
2x3 + 6x2 + x
2x3 − 6x2 − x

User Justhecuke
by
5.7k points

2 Answers

3 votes
The correct answer is choice 4.
You can factor f(x) to 6x^2(2x^3+6x^2-x)
Divide that by 6x^2 and you get choice 4.
User MarGin
by
5.2k points
0 votes

For this case we have the following functions:


f (x) = 12x ^ 5-36x ^ 4-6x ^ 3\\g (x) = 6x ^ 2

We must find the value of:
\frac {f (x)} {g (x)}, then:


\frac {f (x)} {g (x)} = \frac {12x ^ 5-36x ^ 4-6x ^ 3} {6x ^ 2} = \frac {12x ^ 5} {6x ^ 2} - \frac {36x ^ 4} {6x ^ 2} - \frac {6x ^ 3} {6x ^ 2}

For division of powers of the same base, the same base is placed and the exponents are subtracted:


\frac {f (x)} {g (x)} = 2x ^ 3-6x ^ 2-x

Answer:

Option D

User LucyViolet
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.